Association Between Health Literacy and Enhanced Recovery After Surgery Protocol Adherence and Postoperative Outcomes Among Patients Undergoing Colorectal Cancer Surgery: A Prospective Cohort Study. (February 2022) - Qin, Pei-Pei; Jin, Ju-Ying; Min, Su; Wang, Wen-Jian; Shen, Yi-Wei
Abstract : BACKGROUND: Low health literacy (HL) adversely affects medical adherence and health outcomes in patients with chronic diseases. However, the association between HL and enhanced recovery after surgery (ERAS) adherence and postoperative outcomes has not been investigated in patients undergoing colorectal surgery. METHODS: The data of all patients from a single academic institution who underwent colorectal surgery on an ERAS pathway from January 2019 to July 2020 were prospectively collected. HL levels were assessed using the Brief Health Literacy Screen (BHLS), a proven tool that was used by surgeons after recruitment. According to the HL score, the participants were categorized into low HL (⩽9 points) and high HL (10–15 points) groups. The primary outcome was ERAS adherence. Adherence was measured in 22 perioperative elements, and high adherence was defined as adherence to 17 to 22 elements. Secondary outcomes included postoperative complications, hospital length of stay (LOS), hospital charges, mortality, and readmissions. RESULTS: Of the 865 eligible patients, the high HL group consisted of 329 patients (38.0%), and the low HL group contained 536 patients (62.0%). After propensity score matching (1:1), 240 unique pairs of patients with similar characteristics were selected. Patients with high HL levels had a significantly higher rate of high adherence to ERAS standards than those with low HL levels (55% vs 25.8%; adjusted P < .001). In terms of adherence to each item, high HL levels were significantly associated with higher adherence to preoperative optimization (90.8% vs 71.7%; adjusted P < .001), postoperative gum chewing (59.2% vs 44.6%; adjusted P = .01), early feeding (59.2% vs 31.3%; adjusted P < .001), and early mobilization (56.7% vs 30.4%; adjusted P < .001). In the overall study population, adjusted logistic regression analyses also showed that high HL levels were associated with a significantly increased rate of high adherence when compared with low HL levels (adjusted odds ratio [OR], 3.57; 95% confidence interval (CI), 2.50–5.09; P < .001). In addition, low HL levels were associated with a significantly higher incidence of postoperative complications (32.1% vs 20.8%; P < .01), longer hospital LOS (9 [interquartile range IQR, 7–11] vs 7 [IQR, 6–9] d; P < .001), and higher hospital charges (10, 489 [IQR, 8995–11942] vs 8466 [IQR, 7733–9384] dollar; P < .001) among propensity-matched patients. However, there were no differences in the mortality and readmission rates between the HL groups. CONCLUSIONS: Low HL levels were associated with lower adherence to ERAS elements among propensity-matched patients undergoing colorectal surgery.